A note on the Meir-Keeler theorem in the context of b-metric spaces - Pavlović, Mirjana V.; Radenović, Stojan N. (Vojnotehnički glasnik / Military Technical Courier, 2018)
In this note we consider the famous Meir-Keeler’s theorem in the context of b-metric spaces. Our result generalizes, improves, compliments, unifies and enriches several known ones in the existing literature. Also, our proof of Meir-Keeler’s theorem in the context of standard metric spaces is much shorter and nicer than the ones in (Ćirić, 2003) and (Meir & Keeler, 1969, pp.326-329).
Keywords: b-metric space; b-complete; b-Cauchy; Meir-Keeler conditions; Picard sequence